Radikalik UV polimerizasyon ile siloksan modifiye edilmiş Bisfenol A ve/ veya 6F Bisfenol A hibrit kaplamaların hazırlanması, karakterizasyonu ve uygulanmaları - Kuğu, Murat (My University, 2004)
Son otuz yıldan beri, çevre ve halk sağlığı şirketleri, kaplama endüstrisine çok düşük veya sıfır uçucu organik bileşik emisyonuna sahip kaplama ürünleri geliştirmek ve üretmek için baskı yapmaktadırlar. Bu baskılar ve petrole dayalı enerjide karşılaşılan güçlükler sebebiyle şirketler farklı arayışlara girmişlerdir. Araştırmalar sonucunda, yüksek enerjili radyasyonla üretim yapan teknolojinin, düşük enerji ihtiyacı, ürün kalitesindeki mükemmellik, çevreye verdiği zararının çok az olması ve bunun gibi özellikleri sebebiyle, şirketlerin ihtiyaçlarına cevap veren bir sektör olduğuna karar verilmiştir. Radyasyonla sertleştirme ( Ultraviolet, UV ve Electron Beam, EB ) kaplamalar %100'e yakın katı içeriğine sahip olarak formülize edilmiştir.Sonuç olarak, kaplama endüstrisinde ( ahşap, metal, kağıt, plastik ) radyasyonla sertleşebilen kaplamaların pazar payı, geçen 20 yıldan beri heryıl yaklaşık %5 oranında artmıştır. UV ışınları ve Elektron Demeti (EB) ile sertleşebilen kaplama sistemlerinde en az 3 temel bileşen bulunmaktadır.Bunlar sırası ile, doymamış oligomerler, çapraz bağlama amaçlı ve/ veya çözücü olarak kullanılan reaktif seyrelticiler ve fotobaşaltıcılardır .Bunlara ek olarak kaplamanın amacına göre pigmentler, boyalar, ıslatıcılar gibi reaktif olmayan çeşitli katkı malzemeleri de kullanılmaktadır. Çalışmamızın ilk aşamasında, siloksan fonksiyonel Bisfenol A hazırlandı. Sentez, iki basamaklı reaksiyondan oluşmaktadır. İlk olarak 2,2'-Bis ( 4-ß-hydroxy ethoxy) phenyl propane (HEPA) sentezlendi. İkinci olarak, HEPA'nın uçları (3-izosiyanatopropil) trimetoksisilan (IPTMS)'nın -NCO gruplarıyla modifiye edildi ve HEPA Üretan elde edildi. Çalışmamızın ikinci aşamasında, Standart karışım (epoksi oligomer + hekzan diol diakrilat + fotobaşlatıcı ) olarak adlandırdığımız karışıma HEPA Ürethane ve Metakriloiloksi propil Trimetoksi Silan (MPTMS)'dan oluşan karışımdan farklı oranlarda eklendi ve farklı formülasyonlar( 0%, 5%, 10%, 20%, 30%) hazırlandı. Bu formülasyonların bir kısmı teflon kalıplar üzerine dökülerek, termal gravimetrik analiz (TGA) için testi için serbest film elde etmek amacıyla kullanıldı. Filmleri polimerleştirmek için 300 W Osraw Ultravitalux lambası UV kaynağı olarak kullanıldı. Formülasyonların diğer kısmıda alüminyum plakalar üzerine kaplandı ve UV ışığı ile polimerleştirildi. Bu polimerik filmlerin yüzey kaplama malzemesi olarak göstermiş olduğu özellikler, ASTM ve DIN yöntemleri ile incelendi. Kasım 2004 Murat KUĞU

In the last thirty years, enviromental and human health companies have forced coating industries to develop and produce coating products having lower or zero volatile organic compound emission.The companies have started to research different technology because of these forces and difficulties in using of energy depending on petrol. At the end of the researching, the technology having radiation with high enegry, because of low enegry requirement, excellent product quality, very little harmful for enviromental and other properties, gave neccessary answers for requirement of companies. Radiation curable ( Ultraviolet, UV ve Electron Beam, EB ) coatings are prepared as having 100 % solid content[1,2]. As a result, the market part of radiation curable coating in coating industry ( wood, metal, paper, plastic ) have increased every year about 5 % in the decade years. UV and EB curable coating systems have the least 3 basic component. These are unsaturated oligomers, reactive diluents using for crosslinking and / or as solvent and photoinitiators, respectively. Besides, according to purpose of coating are used various non-reactive additives such as pigments, dyes, wetting agents. In the first step of our study, siloxane functional bisphenol A was synthesized. The synthesis have a reaction consisting of two steps. Firstly, 2,2'-Bis ( 4-ß-hydroxy ethoxy) phenyl propane (HEPA) was synthesized. Secondly, the terminals of HEPA was modified with the -NCO groups of (3-isocyanatopropyl) trimethoxysilane (IPTMS) and HEPA Urethane was synthesized. In the second step, A mixture that consist of HEPA Urethane and Methacryloyloxy propyl trimethoxy silan (MPTMS) was added to standart mixture ( epoxy oligomer + hexane diol diacrylate + photoinitiator) in different ratios and in this way, ıt was prepared 5 different formülations ( 0%, 5%, 10%, 20%, 30%). Homogeneously mixed liquid samples were poured into teflon coated molds to obtain free films for Thermal Gravimetry Analyse (TGA) test. These samples were irradiated for 3 minutes from one side, using 300 W Osraw Ultravitalux lamp as the UV-source. Besides, It was obtained UV-cured polymeric films on aluminium plates. The surface material properties of these films are investigated. For that, It was used ASTM and DIN methods. Kasım 2004 Murat KUĞU In the last thirty years, enviromental and human health companies have forced coating industries to develop and produce coating products having lower or zero volatile organic compound emission.The companies have started to research different technology because of these forces and difficulties in using of energy depending on petrol. At the end of the researching, the technology having radiation with high enegry, because of low enegry requirement, excellent product quality, very little harmful for enviromental and other properties, gave neccessary answers for requirement of companies. Radiation curable ( Ultraviolet, UV ve Electron Beam, EB ) coatings are prepared as having 100 % solid content[1,2]. As a result, the market part of radiation curable coating in coating industry ( wood, metal, paper, plastic ) have increased every year about 5 % in the decade years. UV and EB curable coating systems have the least 3 basic component. These are unsaturated oligomers, reactive diluents using for crosslinking and / or as solvent and photoinitiators, respectively. Besides, according to purpose of coating are used various non-reactive additives such as pigments, dyes, wetting agents. In the first step of our study, siloxane functional bisphenol A was synthesized. The synthesis have a reaction consisting of two steps. Firstly, 2,2'-Bis ( 4-ß-hydroxy ethoxy) phenyl propane (HEPA) was synthesized. Secondly, the terminals of HEPA was modified with the -NCO groups of (3-isocyanatopropyl) trimethoxysilane (IPTMS) and HEPA Urethane was synthesized. In the second step, A mixture that consist of HEPA Urethane and Methacryloyloxy propyl trimethoxy silan (MPTMS) was added to standart mixture ( epoxy oligomer + hexane diol diacrylate + photoinitiator) in different ratios and in this way, ıt was prepared 5 different formülations ( 0%, 5%, 10%, 20%, 30%). Homogeneously mixed liquid samples were poured into teflon coated molds to obtain free films for Thermal Gravimetry Analyse (TGA) test. These samples were irradiated for 3 minutes from one side, using 300 W Osraw Ultravitalux lamp as the UV-source. Besides, It was obtained UV-cured polymeric films on aluminium plates. The surface material properties of these films are investigated. For that, It was used ASTM and DIN methods.
Keywords: Kimya mühendisliği ve ilgili konular; Organik Kimya; Organik kimyasallar; Sanayi kimyasalları teknolojisi